Medicinal leeches for the treatment of venous congestion and hematoma after plastic reconstructive surgery - Riede, Friederike Sophie; Koenen, Wolfgang; Goerdt, Sergij; Ehmke, Heimo; Faulhaber, Jörg (Journal der Deutschen Dermatologischen Gesellschaft, 2010)
Background: Leeches were used for medical purposes as long as 2 000 years ago in ancient Egypt. In recent years the use of medicinal leeches became rather popular again, e. g. to improve blood circulation in ischemic tissue after reconstructive plastic surgery. Patients and Methods: In a single center, retrospective study 23 consecutive cases were analyzed in which medicinal leeches had been used therapeutically after plastic reconstructive surgery. All cases were categorized regarding the indication for leech therapy, the onset, the duration, the number of leeches and the number of sessions. Results: Among the group of patients there were 7 female and 16 male patients with a mean age of 73 ± 14 years (48-94 years) altogether. The main indications were venous congestion (12/23; 52 %) and hematoma (9/23; 39 %). Two cases were diagnosed with a necrosis of the tip of the flap and therefore received leech therapy (2/23; 9 %). The average number of leeches was 2.6 leeches/session, the number of sessions was 1.7 ± 0.8. 20/23 patients (87 %) showed a restitutio ad integrum after leech therapy, in 3/23 patients (13 %) a necrosis of the tip of the flap could not be prevented. A clinical improvement was noticed after an average of 1.1 ± 0.3 days. Conclusions: The early application of medicinal leeches can improve local hemodynamic conditions. Leech therapy is a simple and effective method; the cost efficiency of the treatment is high.